A Structural Insight into Major Groove Directed Binding of Nitrosourea Derivative Nimustine with DNA: A Spectroscopic Study - Agarwal, Shweta; Jangir, Deepak Kumar; Mehrotra, Ranjana; Lohani, Neelam; Rajeswari, M. R. (PLOS ONE, 2014)
Nitrosourea therapeutics occupies a definite place in cancer therapy but its exact mechanism of action has yet to be established. Nimustine, a chloroethyl nitrosourea derivative, is used to treat various types of malignancy including gliomas. The present work focuses on the understanding of nimustine interaction with DNA to delineate its mechanism at molecular level. Attenuated total reflection-Fourier transform infrared (ATR-FTIR) has been used to determine the binding sites of nimustine on DNA. Circular dichroism (CD) spectroscopy has been used to confirm conformational variations in DNA molecule upon nimustine-DNA interaction. Thermodynamic parameters of nimustine-DNA reaction have been calculated by isothermal titration calorimetry. Results of the present study demonstrate that nimustine is not a simple alkylating agent rather it causes major grove-directed-alkylation. Spectroscopic data suggest binding of nimustine with nitrogenous bases guanine (C6 = O6) and thymine (C4 = O4) in DNA major groove. CD spectra of nimustine-DNA complexes point toward the perturbation of native B-conformation of DNA and its partial transition into C-form. Thermodynamically, nimustine-DNA interaction is an entropy driven endothermic reaction, which suggests hydrophobic interaction of nimustine in DNA-major groove pocket. Spectral results suggest base binding and local conformational changes in DNA upon nimustine interaction. Investigation of drug-DNA interaction is an essential part of rational drug designing that also provides information about the drug’s action at molecular level. Results, demonstrated here, may contribute in the development of new nitrosourea therapeutics with better efficacy and fewer side effects.